(untitled) (Research, Society and Development, 2020)
This research has as its thematic delimitation the study about socio-environmental disasters and the implications for health in the Brazilian Amazon region, and brings as a central proposal to understand the social and environmental effects and health of the local population, generated by the wreck of the vessel Haidar to the residents of Vila do Conde - coastal community of the State of Pará. The approach used was quantitative and qualitative research. As for the procedures, field research was chosen. The techniques applied for data collection were semi-structured interviews, application of questionnaires prepared with open and closed questions and records in the field diary. The collected data were organized, categorized and analyzed through content analysis, in a time frame, before, after and the current situation of the disaster. The results showed that the socio-environmental disaster caused health imbalances in the residents of the community, in which 603 medical and hospital visits were quantified.